2018
DOI: 10.3389/fneur.2018.00030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acupuncture on the Recovery Outcomes of Stroke Survivors with Shoulder Pain: A Systematic Review

Abstract: BackgroundPoststroke shoulder pain limits stroke survivors’ physical functioning, impairs their ability to perform daily activities, and compromises their quality of life. The use of acupuncture to manage shoulder pain after a stroke is believed to free the blockage of energy flow and produce analgesic effects, but the evidence is unclear. We therefore conducted a systematic review to summarize the current evidence on the effects of acupuncture on the recovery outcomes of stroke survivors with shoulder pain.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…29 Three of the reviews examined more than one intervention; only data for the interventions that were included in this overview (based on recency and quality on a per intervention basis) were extracted. [30][31][32] Characteristics of the Included Reviews Table 1 summarizes the characteristics of the included reviews. Ten of the included interventions examined nonpharmacological interventions 26,28,[30][31][32][33] and one examined a pharmacological intervention.…”
Section: Review and Primary Study Selectionmentioning
confidence: 99%
“…29 Three of the reviews examined more than one intervention; only data for the interventions that were included in this overview (based on recency and quality on a per intervention basis) were extracted. [30][31][32] Characteristics of the Included Reviews Table 1 summarizes the characteristics of the included reviews. Ten of the included interventions examined nonpharmacological interventions 26,28,[30][31][32][33] and one examined a pharmacological intervention.…”
Section: Review and Primary Study Selectionmentioning
confidence: 99%
“…Most patients’ pain has moderate or severe effects on their daily lives and remains untreated or becomes treatment-resistant [ 30 ]. However, we have no related data to show the effects of acupuncture on post-stroke pain and it needs further researches [ 31 ]. Finally, stroke survivors commonly experience varying degrees of mood disorders including depression and anxiety [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many trials had explored the effect and safety of acupuncture for treating HSP, [11–15] and a recent systematic review also concluded that conventional and electroacupuncture could be effective for management of HSP after stroke; however, very high potential for bias should be considered. [16] Fu's subcutaneous needling (FSN) is a new acupuncture therapy, which mainly acts in the subcutaneous layer, like superficial acupuncture documented in “Huangdi Neijing” and developed from Ashi point therapy and wrist-ankle acupuncture therapy. [17] Evidence has indicated that FSN could rapidly relieve the pain and obviously improve the spasm of soft tissues in treating the soft tissues injuries in clinical practice.…”
Section: Introductionmentioning
confidence: 99%